Nolo Heroizari: Tolkien and Aquinas on the Humble Journey of Master Samwise. (September 2019) - Boyd, Craig A.
In this article, I argue that Tolkien's Sam Gamgee embodies a Thomistic understanding of humility. For Aquinas humility was a proper valuing of the self that helped resist the temptations to overstep the bounds of right reasoning. But the humble person was also, through humility's twin virtue magnanimity, able to do great things by relying on the aid of others. Sam Gamgee's journey from what Tolkien calls "vulgar conceit" to ennobled humility serves as an exemplar of Thomistic virtue.